Pengaruh Kemampuan Komunikasi Matematis dan Kemandirian Belajar terhadap Prestasi Belajar Matematika - Nur Afiani (JKPM (Jurnal Kajian Pendidikan Matematika), 2016)
This research is aimed to analyze the impacts of mathematical communication ability and learning independence on mathematical learning achievement. The method used in this research is a survey methode. Affordable population are all students 7 grade at MTS Darussalam Jakarta. Sample size is 41 respondents, taken by using simple random sampling. The instrument used is  11 essay  test and 25 questionnaire on variables of mathematical communication ability and the result of even mid test on variable mathematical learning achievement. Analysis technique of the data are descriptive satitistic, double correlation coefisien and regression analysis. The research result show that, there are significant impacts of both mathematical communication ability and learning independence on mathematical learning achievement all together.  There are significant impacts of mathematical communication ability on mathematical learning achievement There are significant impacts of learning independence on mathematical learning achievement.